No One Left Behind : Rural Poverty in Indonesia - World Bank (World Bank, Washington, DC, 2020)
Indonesia has sustained robust growth over a long period, and this has enabled millions of citizens to move out of poverty. Indonesia’s gross domestic product (GDP) has risen at an average 5 percent a year since 1990 and 5.3 percent a year after the Asian financial crisis at the end of the 1990s. This growth has been supported by favorable international commodity markets, a large, young population, and a solid macroeconomic policy framework. Although the growth has moderated in the last few years as commodity prices and global financing conditions that had buoyed growth previously have become less favorable, annual GDP growth has still averaged 5 percent since 2014. As a result, GDP per capita is calculated to have grown six fold between 1990 and 2018, while extreme poverty declined from 57 percent to slightly less than 6 percent. However, many Indonesians remain vulnerable, and most of those who have escaped poverty still lack the economic security and well-being of the middle class. Despite the progress in poverty reduction, around 30 percent of Indonesians still risk falling back into poverty or become poor following a financial or nonfinancial shock. In addition, although their number is growing, fewer than a quarter of Indonesians are today free from worry about monetary poverty and therefore belong to the middle or upper class. Joining the middle class is associated with people who have additional disposable income for discretionary expenditures, such as on health care, education, and housing, which directly affect their well-being. While rural areas have also benefited from this broad-based growth, an overwhelming majority of the poor and vulnerable are living in rural areas. Making continued progress in reducing poverty will require that the challenges to improving the living conditions of the poor in rural areas are addressed. Against this backdrop, the objective of this report is to update the knowledge about rural poverty in Indonesia. The report analyzes the trends in rural poverty and inequality, the profile of the rural poor, and drivers of observed poverty reduction. New analysis is combined with syntheses of recent work, especially the recent report on urbanization. The goal is to consolidate relevant material on rural poverty. The final section of the report offers some reflections on future research to deepen the understanding of the challenges and the opportunities involved in reducing rural poverty in Indonesia.